WellNest Care: Patient Status Smart Monitoring - Dyg Norkhairunnisa, Abang Zaidel; Vivian Ping, Thomas; Mohd Ridhuan, Mohd Sharip; Dayang Azra, Awang Mat; Lidyana, Roslan (2025)
This paper aims to propose a patient status monitoring system for smart home healthcare. The proposed configuration monitors the patient's vital signs and activity levels using wireless sensors and Wi-Fi Technologies integrated with closed-circuit television (CCTV) for real-time monitoring. The system collects data from various sensors, including heart rate, concentration of oxygen level, and body temperature. The acquired data are then transmitted to a cloud for analysis and processing. The analyzed data are utilized to provide real-time information on the patient's health state to caregivers and medical experts, enabling prompt actions and medical attention. The system is designed for seamless integration into existing smart home infrastructures and aims to enhance the quality of life and health outcomes for the urban patient population. During testing, a notable inaccuracy affects the precision of the outcomes. The average percentage of inaccuracy for the LM35 was determined to be 4.43%. Meanwhile, the MAX30102, capable of detecting concentration of oxygen level and heart rate, exhibits percentage errors of 0.6% and 9.7%, respectively.